2003
DOI: 10.1021/ja034724x
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of a Calcium-Binding Protein

Abstract: Calcium ions play key roles as structural components in biomineralization and as a second messenger in signaling pathways. We have introduced a de novo designed calcium-binding site into the framework of a non-calcium-binding protein, domain 1 of CD2. The resulting protein selectively binds calcium over magnesium with calcium-binding affinity comparable to that of natural extracellular calcium-binding proteins (K(d) of 50 microM). This experiment is the first successful metalloprotein design that has a high co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(99 citation statements)
references
References 47 publications
(75 reference statements)
5
91
0
1
Order By: Relevance
“…33,44 The calcium dissociation constant for the Dezymer-redesigned protein CD2.Ca1 was reported to be 40 AE 10 lM, 33 which is similar to the calcium dissociation constant of 59 AE 2 lM for the bestredesigned OptGraft protein. Despite some position similarities between our designs and CD2.Ca1, the structural characteristics of these designs are distinctively The current implementation of OptGraft can be used to introduce only binding (not catalytic) pockets onto existing protein scaffolds as all the geometry optimization/energy minimization steps are performed only at the ground state.…”
Section: Summary and Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…33,44 The calcium dissociation constant for the Dezymer-redesigned protein CD2.Ca1 was reported to be 40 AE 10 lM, 33 which is similar to the calcium dissociation constant of 59 AE 2 lM for the bestredesigned OptGraft protein. Despite some position similarities between our designs and CD2.Ca1, the structural characteristics of these designs are distinctively The current implementation of OptGraft can be used to introduce only binding (not catalytic) pockets onto existing protein scaffolds as all the geometry optimization/energy minimization steps are performed only at the ground state.…”
Section: Summary and Discussionmentioning
confidence: 78%
“…This domain has been extensively used as a platform for different protein design endeavors, and it has been shown that it can accommodate different configurations of calcium-binding pockets. [32][33][34][35] Ye et al employed glycine linkers to fuse calcium-binding loop III from calmodulin at three different locations in the first domain of CD2 protein. 34 The results indicated that the redesigned protein gained calcium-binding centers while at the same time the overall conformation of the host protein was minimally disturbed.…”
Section: Optgraft Predictionsmentioning
confidence: 99%
See 3 more Smart Citations